Design of a visitor management device for the intelligent management of national parks in Costa Rica - Chaves-Varela, Gerson (2023)
This article describes the design process for a visitor flow control device for National Parks in Costa Rica. This design seeks to contribute to the work of protected area administrators in terms of information on visitor flow and decision making for the implementation of adaptive management plans that seek the safety and satisfaction of visitors, due to a recent reduction in the number of visitors and a decrease in the capacity of these parks in a sustainable manner. The design process was guided by the Design Thinking methodology, using tools such as referent analysis, perception analysis, technological analysis, ergonomic analysis, among others. The result of this process is a device adaptable to national park visitors and capable of transmitting the user's position to facilitate data management by administrators to identify trends, areas of high density and risk level, streamlining the planning of decision making in the short, medium, and long term. During the design process, product characteristics were defined, such as manufacturing, materials to be used, system operation and some of the experiences to verify with potential users that the product is in sync with the objectives and requirements initially proposed in the project. In addition, a strategic plan is proposed to implement and validate a functional prototype in a national protected area to evaluate in a real environment the operation and iterate, if necessary, the design solution. Through this research a clear advantage of using smart products to improve visitor flow control was identified and the solution created attempts to leverage these advantages to provide protected area managers with a way to maximize their revenue without compromising sustainability or user satisfaction.